PRAGMATICS STRATEGIES IN MEMES: A STUDY OF HUMOR AND SOCIAL COMMENTARY IN ONLINE CULTURE - Rana May Zuhra; Puspita Maharani; Rahayu Wulandari; Hawa Alfina Salsabila; Siregar, Deasy Yunita (Universitas Negeri Medan, 2025)
This research investigates the role of memes as a communication tool in Indonesia, particularly focusing on their ability to convey social and political criticism through humor. Memes have emerged as a significant medium for expressing public opinion and fostering discourse on national issues. Utilizing a qualitative approach, the study analyzes 15 memes collected from social media platforms such as Instagram, TikTok, and Twitter. The analysis employs two pragmatic theories: Implicature Theory and Speech Act Theory, to explore the underlying meanings and social implications of these memes. Findings reveal that memes not only entertain but also engage audiences in critical discussions about societal challenges, reflecting a growing trend of using humor as a means of social commentary. This study contributes to the understanding of meme dynamics in non-Western cultures and highlights their potential in shaping public discourse.